Diagnostico socioeconómico del agronegocio conchero (anadara tuberculosa) en la comuna las huacas del archipielago de Jambelí - Muñoz Suarez, Cindy Mishelle (Machala : Universidad Técnica de Machala, 2018)
Abstract in this work, a diagnosis of the current social and economic situation of the collectors of Concha Prieta (tuberculous Anadara) is made to propose strategies of entrepreneurship administration and innovation in the commune the Huacas with the objectives of To study the socioeconomic aspects of Concha Prieta's collectors (tuberculous Anadara) and to propose the creation of added value as a strategic alternative in the Conchera activity. The Conchera fishery in the Jambelí archipelago in the province of El Oro, represents one of the areas of greatest exploitation and disembarkation of the Conchere resource. According to the statistics of the National Institute of Fisheries and Aquaculture, in the province of El Oro, Puerto Hualtaco is located in the first place with 49% of unloading of tuberculous Anadara, then Puerto Bolívar with 30%, finally Puerto Jelí with 16% and port The nose that has 5% with less disembarkation of the mollusc. In this research, we conducted a survey of 128 closed-type questions addressed to the community members of the island of Las Huacas, the population records were obtained from the vestry of Jambelí, then proceeded to survey the locals in their home and Some in their work. The information obtained was tabulated in a database in Excel, after which it was analyzed in the statistical program SPSS version 24.0 and finally were elaborated tables and graphs for their respective interpretation. In addition, information relating to socioeconomic and production was raised; Reviewing statistical information on institutional platforms such as CNA (National Chamber of Aquaculture), National Fisheries Institute (INP) and FAOSTAT (United Nations Food and Agriculture Organization. It was necessary to collect secondary information, a bibliographical review of high impact indexed journal, publications of studies of qualification and scientific relevance works on topics of socioeconomic impacts, agribusiness of the sector Conchero in the national and international context. The results indicate that more than half of the community members have not formed an agribusiness, indicating a favorable panorama for the implementation of agribusiness. 64.29% of the collectors have received training, however, have not innovated harvesting and presentation of the final product and finally the locals see as an alternative add value to their production. The experience achieved in this research, allows to recommend continuing to follow up the conch collectors of the community "Las Huacas", use a model of agribusiness as an alternative to improve their production and presentation of Final product. It is recommended to look for an alternative to build a health center, and that the student has transportation to attend the schools that are in the commune Costa Rica and others are located in Puerto Hualtaco, Machala. Another recommendation would be for the institutions to provide advice and training to the community members so that they can better exploit the conchere resource, and that the collectors also have knowledge of the lines of credit granted by the Financial institutions.
En este trabajo, se realiza un diagnóstico de la situación social y económica actual de los recolectores de concha prieta (Anadara tuberculosa) para proponer estrategias de emprendimiento administración e innovación en la comuna las Huacas con los objetivos de estudiar los aspectos socioeconómicos de los recolectores de concha prieta (Anadara tuberculosa) y proponer la creación de valor agregado como alternativa estratégica en la actividad conchera. La pesquería conchera en el archipiélago de Jambelí en la Provincia de El Oro, representa una de las zonas de mayor explotación y desembarque del recurso conchero. De acuerdo a las estadísticas del Instituto Nacional de Pesca y Acuacultura, en la provincia de El Oro, puerto Hualtaco se ubica en primer lugar con el 49% de desembarque de Anadara tuberculosa, seguidamente puerto Bolívar con el 30%, finalmente puerto Jelí con 16% y puerto El Morro que tiene el 5% teniendo menores desembarque del molusco. En esta investigación, se realizó una encuesta de 128 preguntas tipo cerrada dirigidas a los Comuneros de la isla Las Huacas, los registros de la población se la obtuvo de la junta parroquial de Jambelí, posteriormente se procedió a encuestar los comuneros en su domicilio y algunos en su trabajo. La información obtenida fue tabulada en una base de datos en Excel, luego de lo cual fue analizada en el programa estadístico SPSS Versión 24.0 y finalmente se elaboraron tablas y gráficas para su respectiva interpretación. Además, se levantó información correspondiente con el ámbito socioeconómico y producción; revisando información estadística de plataformas institucionales como CNA (Cámara Nacional de Acuacultura), Instituto Nacional de Pesca (INP) y FAOSTAT (Organización de las Naciones Unidas para la Alimentación y la Agricultura. Fue necesario recolectar información secundaria, se realizó revisión bibliográfica de revista indexada de alto impacto, publicaciones de trabajos de titulación y trabajos de relevancia científica sobre temas de impactos socioeconómico, agronegocios del sector conchero en el contexto nacional e internacional. Los resultados indican más de la mitad de los comuneros no han conformado un agronegocio, indicando un panorama favorable para la implementación de agronegocios. El 64,29% de los recolectores han recibido capacitación, sin embargo, no han innovado la capturas de cosechas y presentación del producto finales y finalmente los comuneros ven como una alternativa darle valor agregado a su producción. La experiencia alcanzada en la presente investigación, permite recomendar seguir realizando el seguimiento a los recolectores de conchas de la Comuna “Las Huacas”, utilizar un modelo de agronegocio como una alternativa para mejorar su producción y presentación del producto final. Se recomienda buscar una alternativa de construir un centro de salud, y que el estudiante tenga transporte para asistir a los colegios que se encuentran en la comuna Costa Rica y los demás están que esta ubicados en Puerto Hualtaco, Machala. Otra recomendación sería Que las instituciones brinden asesoramiento y capacitación a los comuneros para que puedan explotar de mejor manera el recurso conchero, y que también los recolectores tengan conocimiento sobre las líneas de créditos que otorgan las instituciones financieras.
Keywords: AGRONEGOCIOS; CONCHA; CADENA; PRODUCCIÓN